Formal Verification of a Security Protocol in Vehicular Communication - Almaazmi, Mohamed Adel (2025)
A Master of Science thesis in Computer Engineering by Mohamed Adel Almaazmi entitled, “Formal Verification of a Security Protocol in Vehicular Communication”, submitted in April 2025. Thesis advisor is Dr. Dana Dghaym. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).